Trace metals and their human health risks in sesame seeds from the main cultivation areas of Ethiopia. - Bewketu Mehari; Tarekegn Fentie Yimer; Tihitna Beletkachew; Eyob Alem; Worku Negash; Mengistu Mulu; Dereje Yenealem; Ayalnesh Miretie (PLoS ONE)
Sesame (Sesamum indicum L.) is a major oilseed crop globally, and white sesame is a key contributor to the foreign exchange earnings of Ethiopia. The main production districts of white sesame in Ethiopia are Humera, Metema, Tegedie, Mirab-Armachiho and Tachi-Armaciho. This study assessed the levels of trace metals (Fe, Cu, Zn, Mn and Ni) in white sesame seeds from these regions and evaluated the associated health risks to consumers. A total of 53 samples were collected from 19 farmer villages across the five districts. Homogenized samples from each village were analyzed using the acid digestion method followed by flame atomic absorption spectroscopy (FAAS). The limit of detection of the method ranged from 0.75 to 865 mg/kg, and the limit of quantitation ranged from 2.55 to 28.8 mg/kg for the different elements analyzed. The recovery of the method was in the range of 90.9‒99.6%. The results showed trace metal levels ranging from 164 ± 6 to 381 ± 4 mg/kg for Fe, 94.0 ± 1.9 to 126 ± 0.8 mg/kg for Zn, 11.8 ± 0.4 to 14.2 ± 0.4 mg/kg for Cu, 11.9 ± 0.9 to 15.0 ± 0.7 mg/kg for Mn and 16.2 ± 1.1 to 21.0 ± 1.2 mg/kg for Ni across the production districts. One-way ANOVA revealed significant differences (p <  0.05) in trace metal concentrations among the districts, indicating a geographical effect on the trace metal content of sesame. Importantly, the study found no non-carcinogenic health risks from the analyzed metals for either adult or child consumers. These findings suggest that the trace metal levels in the sesame seeds are within safe limits for human consumption.